Auditing in Public Sector Bodies and Their Role in Combating Financial Corruption: Reading on Some International Experiences - بلبوزي أسماء; لعلايبية مالك (Finance and Business Economies Review, 2023)
This research paper aims to show the role of auditing in combating financial corruption in public sector bodies in the light of international experiences. The study concluded that the audit has a major role in combating corruption in public sector bodies, as it is an effective monitoring tool, where international experiences prove this, through the advanced ranks achieved by these countries in the Corruption Perceptions Index issued by Transparency International, and to eliminate the ambiguity of legality and appropriateness known by the financial control in Algeria we need to adopt the audit in the public sector to combat financial corruption through the review of performance, efficiency and effectiveness